Tribals, Forests and Resource Conflicts in Kerala, India: The Status Quo of Policy Change - A. DAMODARAN (Oxford Development Studies, Vol. 34, No. 3, September 2006, 2006)
One of the constraints in policy analysis of tribal issues in India has been the lack of analytical approaches that have looked at the existential problem of tribal communities in an integrated manner. While restrictive forest policies have played a major role in fomenting tribal unrest in India and other parts of the world, the part played by "poorly designed" development programmes in creating the impasse cannot be ignored. With reference to the District of Wayanad in north Kerala, India, it is argued that natural resource conflicts involving tribal communities have their roots in both restrictive forest policies and misplaced development strategies. While it is true that, in recent times, there has been a serious effort in India to open forests to tribal communities, this has not been accompanied by a change in basic development thinking. It is argued that, for a paradigm change in policy to occur, tribal communities need to be nurtured in forest settings. This is particularly relevant at this juncture, when the ideal of "biodiversity conservation" is considered to be the defining mark of sustainable development in the "natural resource-rich" countries of the Sout